The Effect of Facilitating Conditions on Implementing A Regional Financial Management Information System (SIPKD) at Padang City Hall Goverment - Nurhikmah Nurhikmah; Febryandhie Ananda (Basic and Applied Accounting Research Journal, 2021)
The government is trying to realize the excellent service to the community by building information technology in finance or accounting in relation to the financial management area. The purpose of this study to determine the influence of facilitating conditions on implementing a regional financial management information system (SIPKD). This research was conducted at Padang City Hall government. One hundred questionnaires have sent to companies, and only 80 questionnaires can be used. The data collection techniques uses aquestionnaire prepared by using the UTAUT konstuk. Quantitative analysis techniques and simple linear regression analysis is used as a data analysis technique with the help of SPSS 25. The analysis shows the facilitating conditions positive influence on the implementing a regional financial management information system (SIPKD).